Treshold effects in real interest rate parity for the Central and Eastern European countries - Chi-Wei, Su; Hsu-Ling, Chang; Pei-Long, Shen (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
This study applies a nonlinear threshold unit-root test to assess the nonstationary properties of the real interest rate parity (RIRP) for twelve Central and Eastern European (CEE) countries. We find that the non-linear threshold unit-root test has a higher power than the linear method suggested by Caner and Hansen (2001) if the true data generating process of real interest rate convergence is in fact a stationary nonlinear process. We examine the validity of RIRP from the nonlinear point of view and provide robust evidence which clearly indicates that RIRP holds true for nine countries. Our findings point out that real interest rate convergence is mean reversion towards RIRP equilibrium values in a nonlinear way
Argumenta Oeconomica, 2012, Nr 2 (29), s. 77-88
Keywords: nonlinear threshold unit-root test; real interest rate parity; interest rate; real convergence; linear models; stopa procentowa; konwergencja realna; modele liniowe